C++ for dummies - Davis, Stephen R., 1956- 4 0 16; 5 (Hoboken, NJ : John Wiley & Sons, Inc., 2014)
A guide to using C++ programming that includes definitions of expressions and terms, instructions for using the different features of C++, advice on avoiding bugs, and other related topics.
Previous edition: 2009.;Includes index.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; C++ (Computer program language);C++ (Computer program language); 20; 2